A política de recuperação intensiva no Estado de São Paulo: um estudo de caso sobre os sentidos de professores do Ensino Fundamental - Schermack, Lúcia Veiga (2015)
This study aimed to investigate the meanings attributed by teachers on intensive recovery policy and its implementation in a state school in elementary school in São Paulo.Specific objectives were defined: to know as intensive recovery policy was implemented in school, in relation to the characteristics and forms of organization of educational work as well as understand the challenges faced by teachers in action with students of intensive recovery class and the possibilities of action to deal with the problems encountered in the educational process. The research set up with a case study and was based on the Theory Historical-cultural. Three teachers participated in this study and used procedures involved semi-structured interviews, participant observation and records in field diaries. The results indicated that: a) The intensive recovery policy was perceived positively in terms of their objective, but there were critical especially on the need to do it as soon as difficulties are evidenced learning and not in later years; b) Significant changes in the organization of pedagogical work in school; c) the challenges encountered involved aspects such as heterogeneity of learning difficulties presented by the students, conflicts with the management team, discontinuity in the educational support offered by assistant professors because of high turnover; d) Were observed individual forms of resistance and actions and group that aimed to build strategies to deal with the problems encountered in the process. The teachers evaluated that although students have achieved significant progress in relation to learning, many still could not meet the expected requirements for the year were enrolled. It is concluded that intensive recovery policy, as it is configured, can not achieve its goals, which points to the need to critically examine the many factors involved in the production and perpetuation of not learn in school.